1997
DOI: 10.1523/jneurosci.17-11-04236.1997
|View full text |Cite
|
Sign up to set email alerts
|

A New Form of Inherited Red-Blindness Identified in Zebrafish

Abstract: A red-blind zebrafish mutant, partial optokinetic response b (pob), has been isolated by measuring eye movements of larvae in a three-generation screen for recessive mutations affecting the visual system. pob larvae exhibit eye movements in response to rotating black and white stripes illuminated with white light, but they do not move their eyes when the stripes are illuminated with red light. Physiological, immunohistochemical, and in situ hybridization analyses of pob retinas showed a selective loss of red-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 26 publications
1
84
0
Order By: Relevance
“…48 In addition, OKR was also useful in isolating a colour-blind mutant by changing the colour of visual stimulus. 49 In summary, the OKR appears to result in more a robust, reliable, and quantifiable behavioural data compared with other methods described below, especially after automated commercial systems have become available. 3,49 Optomotor response (OMR)…”
Section: Okrmentioning
confidence: 92%
“…48 In addition, OKR was also useful in isolating a colour-blind mutant by changing the colour of visual stimulus. 49 In summary, the OKR appears to result in more a robust, reliable, and quantifiable behavioural data compared with other methods described below, especially after automated commercial systems have become available. 3,49 Optomotor response (OMR)…”
Section: Okrmentioning
confidence: 92%
“…In such a screen, Brockerhoff et al (1997) identified the red-blind mutant partial optokinetic response b (pob) by screening for OKR behavior under red illumination. Homozygous pob larva showed a normal response to white light but failed to execute an OKR under red illumination.…”
Section: Mutations Affecting Specific Cell Types Of the Outer Retinamentioning
confidence: 99%
“…Common behavioral tests that were already used to investigate the visual system of zebrafish larvae or to isolate recessive mutations in large-scale, forward genetic screens include the optokinetic and the optomotor response (e.g. Brockerhoff et al, 1997;Gross et al, 2005;Muto et al, 2005;Neuhauss et al, 1999). These assays are both robust and therefore well suited for high-throughput screening of larvae.…”
Section: Introductionmentioning
confidence: 99%
“…The optokinetic response (OKR) has proven to be particularly useful for testing vision of zebrafish larvae (Beck et al, 2004;Brockerhoff et al, 1997;Gross et al, 2005;Muto et al, 2005;Neuhauss et al, 1999;Rinner et al, 2005). The OKR is a stereotyped eye movement elicited by whole-field motion of the visual surround.…”
Section: Introductionmentioning
confidence: 99%